2021
DOI: 10.1002/smll.202104561
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Metal‐Oxide Photocatalyst for H2O2 Production

Abstract: Hydrogen peroxide (H 2 O 2 ) is a mild but versatile oxidizing agent with extensive applications in bleaching, wastewater purification, medical treatment, and chemical synthesis. The state-of-art H 2 O 2 production via anthraquinone oxidation is hardly considered a cost-efficient and environment-friendly process because it requires high energy input and generates hazardous organic wastes. Photocatalytic H 2 O 2 production is a green, sustainable, and inexpensive process which only needs water and gaseous dioxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
159
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(159 citation statements)
references
References 141 publications
0
159
0
Order By: Relevance
“…Currently, H2O2 is produced via anthraquinone (AQ) process [8][9][10] , direct hydrogen-oxygen reaction 11,12 and oxidation of alcohols 13,14 . These methods either demand high energy input or cause environmental pollution, which significantly hinder their largescale application [15][16][17] . Thus, it is urgent to develop an economic, efficient and eco-friendly method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, H2O2 is produced via anthraquinone (AQ) process [8][9][10] , direct hydrogen-oxygen reaction 11,12 and oxidation of alcohols 13,14 . These methods either demand high energy input or cause environmental pollution, which significantly hinder their largescale application [15][16][17] . Thus, it is urgent to develop an economic, efficient and eco-friendly method.…”
mentioning
confidence: 99%
“…Photocatalysis is a green and sustainable method to produce H2O2 since it is powered by inexhaustible sunlight 18 . Moreover, it also reduces our energy reliance on unsustainable fossil fuels and alleviates environmental pollution 15,19,20 . To date, various semiconductors have been developed for photocatalytic H2O2 production, including TiO2 13,16,21 , ZnO [22][23][24] , g-C3N4 [25][26][27] , CdS 28,29 , graphene 30,31 and BiVO4 32 .…”
mentioning
confidence: 99%
“…As speculated, the precursor TPA1, which mainly absorbed UV light, almost showed no photocatalytic reactivity (Table 2, entry 7). Moreover, control experiments revealed that in the absence of TPA-MPs, visible-light, air or citric acid, the reaction proceeded rather sluggishly and only a small amount of the product was obtained (Table 2, entries [8][9][10][11]. These control experiments demonstrated that the TPA-MP catalyst, visible-light, air and citric acid decisively contribute to the photocatalytic reaction.…”
Section: Synthesis and Characterization Of Tpa-mpsmentioning
confidence: 96%
“…4 Thus, it is still highly desirable to develop efficient heterogeneous photocatalysts that are free of precious metals, inexpensive, stable, and recyclable, to decrease the processing costs in large-scale synthesis. 5 To this end, nonprecious metal-based semiconductors (such as bismuth-based nanomaterials, 6 metal sulfides, 7 metal oxides, 8 transition metal dichalcogenides, 9 etc. ) have emerged as promising candidates for replacing expensive and toxic precious metal-based complexes and organic dyes, which, however, are facing problems such as limited visible-light absorption and photocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The water-induced H 2 O 2 production and the H 2 O 2 -induced luminescence were experimentally studied using single-layered ionogel films (size: 13 mm  7 mm  0.5 mm). An ionogel film containing CaO 2 was placed in deionized water and the H 2 O 2 production was monitored by the cerium sulfate titration method 43,44 using a previously established calibration curve (Fig. S5, ESI †).…”
Section: Self-reporting Mechanism In Underwater Hi-skinsmentioning
confidence: 99%